KONSEP PENDIDIKAN RELIGIUS RASIONAL: STUDI PEMIKIRAN BUYA HAMKA DAN MOHAMMAD NATSIR - Agung Wahyu Utomo; Mohamad Ali; Muh. Nur Rochim Maksum (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
This study aims to find out the thoughts of Buya Hamka and Mohammad Natsir regarding rational religious Islamic education and identify similarities and differences in the thoughts of the two figures regarding rational religious Islamic education. This research is motivated by two main problems, namely the weak vision of Islamic education and epistemological problems in dichotomous Islamic scholarship. Therefore, the concept of rational religious Islamic education which combines worldly and spiritual elements is one of the solutions in the midst of educational backwardness. Buya Hamka and Mohammad Natsir are national Islamic figures who have a high role in education in Indonesia. This type of research is a type of library research. The research approach in this study used historical and philosophical approaches and data analysis using content and comparative analysis. The results of this study conclude that the concept of thinking of rational religious Islamic education according to Buya Hamka and Mohammad Natsir is guidance that combines ukhrawi elements (morals, spiritual, emotional) and worldly elements (mind, body, skills) based on monotheism to complement nature and lead humans to fitrah original. Then the similarities of the two concepts are found in meaning, educational goals, student subjects, and material that must include religious and world knowledge. While the differences seen in the curriculum, teachers and learning methods.Keywords: Educational Thought, Religious-Rational, Buya Hamka, Mohammad NatsirÂ